Financial distress, cash holding, and its effect on earnings management with internal control as a moderator - Verrel, Christopher; Setyawan, Ignatius Roni (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study aims to analyze the effect of financial distress and cash holding on earnings management, with internal control as a moderating variable. The research seeks to explain how financial conditions and liquidity influence managerial decisions in presenting financial statements. Methodology/Approach: The study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) that consistently published annual reports from 2021–2023, totaling 130 firms. Data were obtained from audited financial statements through the official IDX database. Multiple linear regression is used to examine the direct effects of financial distress and cash holding on earnings management, while moderated regression analysis tests the moderating role of internal control. Results/Findings: The results show that financial distress has a positive effect on earnings management, indicating a higher likelihood of manipulation when firms face financial pressure. Cash holding has a negative effect on earnings management, suggesting that higher liquidity reduces incentives to manipulate earnings. Internal control does not moderate the relationship between financial distress, cash holding, and earnings management. Conclusion: Financial distress and cash holding significantly influence earnings management, but internal control does not act as a moderating factor. Limitations: This study is limited to manufacturing firms during 2021–2023, so results may differ in other sectors or periods. Contribution: This study contributes by examining accrual earnings management with internal control as a moderating variable, a combination that remains underexplored in prior research.